FTO Biology and Obesity: Why Do a Billion of Us Weigh 3 kg More? - Cheung, Man-Ka M.; Yeo, Giles (Frontiers in Endocrinology, 2011)
Few would dispute that the current obesity epidemic has been driven by lifestyle and environmental changes. However, it is clear that individuals respond differently to these ‘obesigenic’ changes and this variation in response has a strong genetic element. Genome-wide association studies have revealed that single nucleotide polymorphisms (SNPs) in Fat mass and obesity associated transcript (FTO) are robustly associated with body mass index and obesity. Although the effect of these risk alleles are modest, with heterozygous and homozygous carriers weighing approximately 1.5kg and 3kg more respectively, there are an estimated one billion homozygous carriers in the world, spanning multiple different ethnicities and populations. Yet despite its broad impact, the biological function of FTO, particularly its role in controlling energy balance, remains unknown. Although the study of severe mendelian obesity has been invaluable in illuminating critical pathways controlling food intake, the major burden of disease is carried by those of us with ‘common obesity’, which to date has resisted yielding meaningful biological insights. FTO has at last given us a handle on a huge, worldwide, common problem. In this review, we focus on the available genetic and in vivo evidence to date that implicates FTO in the control of energy balance.